Epoxy/copper oxide composite coating for marine application - Kautsar Tabri; Nor Yuliana Yuhana; Jafreena Adira Jaafar; Ahmad Faiz Al Shafiei; Mohammad Aslamilie Mohd Suhil (Penerbit Universiti Kebangsaan Malaysia, 2021)
This research investigated the usage of cuprous oxide powder as filler for epoxy in marine coating industries. The basic formulation consist of cuprous oxide powder, epoxy pre-polymer, and the curing agent. The main manipulation variable in this research is the quantity of cuprous oxide added into the epoxy resin, which varies from 2, 5, 7, 9, and 11 per hundred gram of epoxy resin (phr). Polyether (amine) was used as the curing agent at equivalent molar ratio. Mechanical stirring was used to achieve dispersion. The samples were cured at room temperature for one week before characterization. Differential scanning calorimetry (DSC), scanning electron microscopy (SEM), infrared spectroscopy (FTIR), X-ray diffraction (XRD), drop shape, water and brine absorption, hardness, and abrasion analysis were used. Drop shape analysis exhibited the hydrophobicity of the surfaces. According to water and brine absorption test that was carried out, it is found that the unmodified epoxy sample has the lowest absorption of water and brine. The composite coating, which underwent abrasion test, exhibited increasing hydrophobicity of the surface directed on the electrical wave generator in 5 days.